The Effect Of Effleurage On Pain Level Reduce In Active Phase I Of Normal Delivery: Literature Review - Diyana Wati; Istiqomah Istiqomah; Nurul Hidayah (Sean Institute, 2023)
Background: The high maternal mortality is caused by severe pain during childbirth. Labor pain also causes various kinds of problems and disorders in childbirth, especially psychological problems. In order to reduce labor pain, there are two ways, namely pharmacological and non-pharmacological, one of which is using effleurage message. Objectives: To determine the effect of effleurage on reducing the level of pain in the active phase of the first stage of normal labor: Literature Review. Method: Literature Review research method with PICOS (T) technique. Research sources using electronic based such as Google Scholar with DOI. The search keywords were Maternal Maternity, Stage I, Active Phase, effleurage, Progress of labor. Inclusion criteria physiological childbirth without complications and complications with articles published in the last 5 years. Results: From ten articles, it was stated that there was a change in pain after effleurage message by giving message to the abdomen in the form of skin stimulation which was used during labor to reduce pain effectively. Conclusion: There is an effect of effleurage on reducing the level of pain in the active phase of the first stage of normal labor.